2016
DOI: 10.1530/jme-15-0260
|View full text |Cite
|
Sign up to set email alerts
|

60 YEARS OF POMC: Purification and biological characterisation of melanotrophins and corticotrophins

Abstract: The remarkable conservation of the primary structures and anatomical location of dogfish α-melanocyte-stimulating hormone (MSH), corticotrophin-like intermediate lobe peptide (CLIP) and adrenocorticotrophic hormone (ACTH) compared with mammals reinforced the tissue-specific processing hypothesis of ACTH peptides in the pituitary gland. The cloning of dogfish pro-opiomelanocortin (POMC) led to the identification of δ-MSH and simultaneously revealed the high conservation of the γ-MSH sequence during evolution. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 47 publications
(39 reference statements)
1
21
1
1
Order By: Relevance
“…We were surprised to readily detect spectra for β-MSH(1-18) whose existence has been disputed 20 , whereas we did not consistently detect spectra for α-MSH(1-13) which has been the subject of intense study 6,7,35,51,52 since it is produced in mice and suggested by some studies to be more stable than d-a-MSH 35 . Upon manual review, we could indeed detect peaks with m/z and column retention times appropriate for α-MSH.…”
Section: Human Hypothalamic Neurons Appropriately Traffic and Secretecontrasting
confidence: 57%
See 1 more Smart Citation
“…We were surprised to readily detect spectra for β-MSH(1-18) whose existence has been disputed 20 , whereas we did not consistently detect spectra for α-MSH(1-13) which has been the subject of intense study 6,7,35,51,52 since it is produced in mice and suggested by some studies to be more stable than d-a-MSH 35 . Upon manual review, we could indeed detect peaks with m/z and column retention times appropriate for α-MSH.…”
Section: Human Hypothalamic Neurons Appropriately Traffic and Secretecontrasting
confidence: 57%
“…Human hypothalamic POMC neurons might also produce b-MSH 14 , which is associated with human obesity when mutated [15][16][17] and inhibits feeding as potently as a-MSH when injected into mice 17 by activating MC4R [16][17][18] . However, b-MSH is not produced in the rodent brain and its existence and biological relevance in humans is controversial [19][20][21] . Since body weight is sensitive to changes in the concentration of POMC-derived peptides [22][23][24][25][26] , understanding POMC processing can provide insights into molecular mechanisms of obesity that might be therapeutically harnessed 3 .…”
Section: Introductionmentioning
confidence: 99%
“…A final point is that although the N-POMC(1-28) used in the study was synthesised with the correct disulfide bridge arrangements and had been shown previously to be biologically active (Fassnacht et al 2003), the disulfide bridge arrangements in N-POMC are known to be unstable (Lowry 2015). It is thus possible that a rearrangement of the bridges to the 2-8, 20-24 configuration could have occurred and rendered the peptide biologically inactive as found in N-POMC(1-36) (Estivariz et al 1988a).…”
Section: The Pomc -/-Mousementioning
confidence: 99%
“…In 1974, we were successful in isolating a series of novel peptides from porcine pituitary (Bradbury et al 1975(Bradbury et al , 1976b and we observed that a group of them accounted for the sequence of adrenocorticotrophic hormone (ACTH) together with the sequence of lipotropin. At that time, it was not known that ACTH and lipotropin are formed from a common prohormone, although the possibility had been discussed informally at Meetings of the Endocrine Society (see Lowry 2016).…”
mentioning
confidence: 99%